Nomenclatural changes for the genus name Perinetia, with a new replacement name for Perinetia Barnard, 1959 (Crustacea: Isopoda: Oniscidea: Philosciidae) - Xing, Ji-Chun; Chen, Xiang-Sheng (Zootaxa, 2013)
The name Perinetia was originally introduced by Collenette (1936) for a genus with the type species Perinetia leucocloea Collenette, 1936 in Lepidoptera (Insecta). The name Perinetia was subsequently used by other authors in other animal groups, i.e. Perinetia Seyrig, 1952 (Insecta: Hymenoptera), Perinetia Lallemand and Synave, 1954 (Insecta: Hemiptera), Perinetia Barnard, 1959 (Crustacea: Isopoda), Perinetia Descamps, 1964 (Insecta: Orthoptera), and Perinetia Domergue, 1988 (Reptilia: Lacertilia). According to Article 60 of the International Code of Zoological Nomenclature (ICZN, 1999), Perinetia Collenette, 1936, has priority, with the other names to be treated as junior homonyms. The nomenclature of four of these junior homonyms: Perinetia Seyrig, 1952, Perinetia Lallemand and Synave, 1954, Perinetia Descamps, 1964, and Perinetia Domergue, 1988, have been resolved by Kocak and Kemal (2008), Demir and Özdikmen (2009), Descamps and Wintrebert (1965), and Domergue and Bour (1989). Recently, Özdikmen (2008) proposed a new generic name Descampsiella to replace Perinetella Descamps and Wintrebert, 1965. Only Perinetia Barnard, 1959 is still used as valid generic name.